Role of l-carnitine in sports performance: Focus on ergogenic aid and antioxidant - Sung, D.J.; Kim, S.; Kim, J.; An, H.S.; So, W. Y. (Science & Sports, 2016)
Objectives: The purpose of this review is to examine the antioxidant effects of l-carnitine (LC) and to highlight its potential application in sports nutrition and exercise performance. News: The benefits of exercise include reduced mortality and decreased prevalence of diseases including cardiovascular disease, diabetes, cancer, and metabolic disease. However, exercise can induce overproduction of reactive oxygen species (ROS) through diverse pathways that decrease skeletal muscle contraction. In addition, overproduction of ROS can negatively affect physical performance by inversing force production of skeletal muscles, initiating quick prompting of fatigue, and causing oxidation-induced damage by lipid and protein peroxidation. Prospect: LC is an endogenous substance that is necessary for the ß-oxidation of fatty acids, and has mainly been studied in the field of sports nutrition because of its glycogen-sparing effect. LC achieves this effect by promoting inhibition of glycolysis, increasing fatty acid metabolism, and acting as an ergogenic aid to delay fatigue and improve physical performance. Results from a recent study suggested that LC consumption was advantageous in inhibiting oxidative stress and activating endogenous antioxidant activity through its role as an antioxidant. However, research on the antioxidant role of LC in the field of exercise science and sports nutrition is currently insufficient. Conclusion: This review discusses research findings on ROS regulation of LC from both basic and sports science fields. It will highlight the role of LC as an antioxidant and ergogenic aid to improve physical performance and control oxidative stress.